Incidence of aplastic anemia and agranulocytosis in Latin America: the LATIN study - Nelson Hamerschlak; Eliane Maluf; Ricardo Pasquini; José Eluf-Neto; Frederico Rafael Moreira; Alexandre Biasi Cavalcanti; Íria Ruriko Okano; Roberto Passeto Falcão; Marimília Teixeira Pita; Sandra Regina Loggetto; Luiz Gastão Rosenfeld; Irene Gyongyvér Heidemarie Lorand-Metze (São Paulo Medical Journal)
CONTEXT AND OBJECTIVE: Aplastic anemia and agranulocytosis are rare but life-threatening disorders, often caused by drugs and other environmental exposures. Reported incidence of these diseases seems to vary between different geographic regions, and few data on their incidence are available for Latin American countries. The aim of this work is to determine the incidence of agranulocytosis and aplastic anemia in Brazil. DESIGN AND SETTING: Incidence study. Seven centers took part in the pilot phase, so as to represent all Brazilian regions. METHODS: Each center conducted an active search for new cases in a defined region by means of regular contacts with all hematologists, main clinical laboratories and clinicians in hospitals of the region. RESULTS: 74 patients with aplastic anemia and 16 with agranulocytosis were identified. Patients with agranulocytosis had a median age of 31 years (interquartile range, IQR: 12.5-48.2); 32.2% were male and 81.2% were white. The median age of aplastic anemia patients was 21 years (IQR 15.0-35.2); 62.2% were male, 50.0% were white and 39.2% mulatto. The incidence of agranulocytosis was estimated to be 0.5 cases per million individuals per year, ranging from 0.0 to 1.1 cases per million per year between regions. The incidence of aplastic anemia was 2.7 cases per million per year, ranging from 1.1 to 7.1 cases per million per year between regions. CONCLUSIONS: Aplastic anemia and agranulocytosis are rare diseases in Brazil. However, there is considerable variability in their incidences between different regions.